2001
DOI: 10.3201/eid0705.017529
|View full text |Cite
|
Sign up to set email alerts
|

Jamestown Canyon Virus: Seroprevalence in Connecticut

Abstract: Emerging Infectious Diseases (bla PER-1 and bla VIM-2) had been detected separately among clinical isolates, underscores the possibility of the emergence of new threatening combinations of resistance determinants among nosocomial pathogens. In fact, the recruitment of similar resistance determinants within a single P. aeruginosa strain can determine a resistance phenotype to virtually all the available antipseudomonal beta-lactams, an occurrence that can be particularly dramatic when, as in the present case, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…In comparison to LACV, however, our JCV cases demonstrated that children were less frequently affected, with no cases in children less than 10 years of age and 63% of cases aged > 40 years. 2427…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to LACV, however, our JCV cases demonstrated that children were less frequently affected, with no cases in children less than 10 years of age and 63% of cases aged > 40 years. 2427…”
Section: Discussionmentioning
confidence: 99%
“…72 A recent report of a Jamestown Canyon virus infection in Montana underscores continued low-level transmission in the northern continental United States. 73 …”
Section: Bunyaviridaementioning
confidence: 99%
“…Confirmatory testing includes anti-JCV IgM antibody screening, with a reflex to PRNT if reactive (3). Seroprevalence studies have demonstrated the presence of neutralizing antibodies to JCV at various rates (3.9 to 17.6% in two studies [5,6]), which suggests that mild or asymptomatic infections occur.…”
Section: Discussionmentioning
confidence: 99%